AN INHERITANCE OF IDIOPATHIC CARDIAC CONDUCTION DISORDERS - S. S. Tretyakova; S. Yu. Nikulina; V. A. Shulman; A. A. Chernova; V. N. Maksimov; M. I. Voevoda; V. N. Chernov (Российский кардиологический журнал)
Aim. To study relationship of idiopathic atrioventricular and intravenricular disorders of cardiac conductivity with mononucleotide polymorhism (MNP) A/G gene TBX5. Material and methods. Totally 260 persons with primary cardiac conductivity disorders included (with AV-blocks of 1, 2, 3 grades, complete His right bundle branch block, complete His left bundle branch block, His rleft anterior bundle branch block) and 257 persons without any cardiovscular diseases. Patients were grouped according to their nosological type, age, gender. All patients underwent standard cardiological examination and molecular-genetic sampling of DNA. Results. The obtained results showed statistically significant predominance of the rare genotype GG (MNP marker rs3825214) gene TBX5 in the group of patients with conduction disorder at left His bundle branch and in subgroup of women with the pathology mentioned.Conclusion. The data obtained makes clear that the presence of GG genotype (rs3825214) gene TBX5 increases chances for idiopathic rhythm disorders development mostly in women. These results can be used during the primary prevention of the pathology mentioned.